Peningkatan Keterampilan Bahasa Inggris untuk Hiburan melalui Modul Pembelajaran Teks Narrative Berbentuk Fabel - Tri Wahyuningsih (MANAZHIM, 2021)
The need for interactive and meaningful distance learning in English lessons is needed to improve students English skills including language skills and formative test-taking skills. This is done by the author through the use of interesting modules or for entertainment for students by utilizing narrative text material in the form of fables. The research method used is descriptive research on 32 students of class XI IPA 2 as a sample of research conducted at SMA Muhammadiyah 1 Taman. The results obtained in the form of observations of the achievement of English language skills including pronunciation, grammar, vocabulary, fluency, understanding are included in the intermediate or intermediate category with an average score of 2, 05. In addition, the students' English skills were also seen from the learning outcomes test data where the percentage of success of students who scored above the KKM (75) was 87.5%, namely 28 students while those who scored below the KKM were 4 students. The conclusion of this study is the achievement of students' English skills after using the narrative text learning module in the form of fables is included in the medium or intermediate category/level 2+ and the percentage of success of formative tests above the KKM is 87.5%.